Essence and elements of crimes in the sphere of official activity - S. Ye. Ablamskyi; M. O. Kolesnyk (Bulletin of Kharkiv National University of Internal Affairs)
It has been argued that an official activity is the service activity of an official determined by the norms of current legislation, which is determined by his/her official position (legal status), and is also aimed at implementing certain tasks and functions assigned to the public authority, institution, organisation, etc. in which he/she works and holds the relevant position. It has been noted that an official has a special legal status, which determines the high risk of committing criminal violations, in particular, crimes.